MICELLAR ENHANCED SYNCHRONOUS FLUORESCENCE FOR THE ASSAY OF SUMATRIPTAN SUCCINATE IN PHARMACEUTICAL TABLETS - FRAIHAT, SAFWAN M. (International Journal of Applied Pharmaceutics, 2019)
Objective: To develop a sensitive, fast and selective method for the determination of sumatriptan succinate (SUM) in pharmaceutical samples. Methods: The method is based on measuring the synchronous fluorescence of SUM using ∆λ of (120 nm) and at a wavelength of excitation and emission of 230 and 325 nm respectively, using Agilent Technology, Cary eclipse, G9800AA model Luminescence spectrometer. Effect of variables on fluorescence emission intensities was studied such as solvent, surfactant, and pH. The proposed method was validated in term of linearity, limit of detection as per the international conference on harmonization guidelines ICH Q2 (R1). Results: The linearity of the method was obtained with a wide range of (50-150) ng/ml with a high value of correlation coefficient value of (0.992). Limits of detection (LOD) and limits of quantitation (LOQ) were found to be 16.3 and 49.5 ng/ml respectively, the mean recovery was found to be 99.1% with low relative standard deviation (% RSD). The method was also compared statistically with the reference method using t-test and f-test, the results show no difference either in pure or pharmaceutical tablets. Conclusion: The obtained results revealed that the developed method can be applied successfully for the determination of SUM in drug formulations samples with good accuracy and precision.